“Desarrollo de tecnologías de bioabonos para el incremento de la productividad; del maíz amarillo duro (zea mayz L.) variedad INIA 622. en la E.E.A Porvenir” - Gaslac Gomez, Sulber (2016)
This investigation work was developed in Agrarian experimental station "El Porvenir'' it is located in San Martín province, for this investigation 1 have the follow goals: Evaluate different bio fertilizers in arder to increase product"1v"ity and econom·1cal benef1t through the organic production of corn (Zea mays L), evaluate and determine the majar dose of bio fertilizer to increase the organic production and make an analysis of the studied economic treatments. For this investigation work 1 used a "blocks design completely at random" (DBCA), which had 6 treatments, which had 4 repetitions: T1: Organic. Gen 8 L.ha-1 , T2: Neen oil 300 CC.ha-1, T3: Biol 160 L.ha-1, T4: Nutriferke 4 L.ha-1, T5 ( witness with fertilizer: N:P:K: (150: 120: 100), Ta: witness. The results was processed and analyzed through the statistic program SPSS22, which 1 obtained the results of statistic parameters; variance analysis to a P< 0,05 and P<0,01, Duncan's Multiple Range Test to a P<0,05, variability coefficient (C.V) and Determination coefficient (R2 ) of evaluated variability. The treatments which had the highest yield were T5 (witness with fertilizer N: P: K: (150: 120: 100) and T3 Biol 160 L.ha-1 ) and 1 obtained the best B/C with O, 33 0,35 and full benefrts of SI. 1556,14 and S/. 1069, 53 suns respectively; the T3 (Biol 160 l.ha-1>, hada height plant of 144.5 cm, corncob height of 52.5 cm; likewise, the treatments T2 (Neen oil 300 CC.ha-1 ), T4 (Nutriferke 4 L.ha~). and T1 (Organic. Gen 8 L.ha-1 ) had lower values B/C of O, 26, O, 2.1 and 0,09 with full benefits of SI. 729, 04, SI. 620, 17 y SI. 281,43 suns respectively. With the Ta (witness Absolut treatment) 1 obtained a negative BIC of -0, 09 with a loss of SI. -214, 49 suns. Considering these treatments with the use of "biol" in arder to increase productivity and control of Spodoptera Frugiperda y Diatraea Saccharalis in the growing com, this is an alternative to use the fertilizers and organic insecticide. Keywords: Biofertilizers, technologie~s. dose, productivity, economic analysis, bioestimulantes, fertilization, organic producís, parameters, lodging, DBCA, oil nen, biol, nutriferke, organic gene, relative humidity.